Պերինատալ կորուստների վերլուծականը - Աբրահամյան, Ռ. Ա.; Ղարդյան, Գ. Կ.; Աբրահամյան, Լ. Ռ.; Աբրահամյան, Ս. Հ.; Աբրահամյան, Գ. Ռ.; Սարգսյան, Շ. Ս․ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Сохранение и улучшение репродуктивного здоровья женщин, подростков и детей является приоритетной задачей, определяющей естественный прирост, демографические показатели и социально-экономическое развитие страны. Ежегодно в РА регистрируется около 4500 перинатальных потерь, большая часть из которых обусловлена неадекватным ведением беременности. Эта проблема становится все более актуальной в связи со снижением рождаемости и ростом смертности. Исходя из социально-экономической безопасности страны, сохранение каждой желанной беременности является стратегической задачей. Maintenance and improvement of reproductive health of women, adolescents and children is a priority issue that predetermines natural growth, demographic indicators and socio-economic development of the country. About 4500 perinatal losses are recorded annually in RA, most of which are caused by inadequate pregnancy control and management. This problem is becoming more urgent due to the decrease in the birth rate and the increase in the mortality rate. Based on the socio-economic security of the country, the preservation of every desired pregnancy is a strategic task.
Keywords: Կլինիկական բժշկություն